Demonstration Learning Berbasis Video Pembelajaran dalam Meningkatkan Hasil Belajar IPA Siswa SMP - Wardah Laily Nur Baity (ScienceEdu: Jurnal Pendidikan IPA, 2019)
Education is guidance carried out by educators consciously on the physical and spiritual development of students as an effort to mature a person through guidance and training. Education in Indonesia continues to grow in line with the times. So that a teacher is required to provide material not only using the lecture method but using other learning methods. The purpose of this study is to find out about improving student learning outcomes by using a demonstration learning method based on learning videos. With the use of student learning videos it is easier to understand the material being taught so that it can link material taught with natural phenomena. In addition students do not feel bored when they are in class and have a high curiosity so students actively ask in class. The use of video learning also improves student learning outcomes. Kata Kunci: demonstration method, learning achievement and learning video